1997
DOI: 10.1002/art.1780400108
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of socioeconomic status, race, and modifiable risk factors to outcomes in patients with systemic lupus erythematosus

Abstract: Objective. To study the relationship of race, socioeconomic status (SES), clinical factors, and psychosocial factors to outcomes in patients with systemic lupus erythematosus (SLE).Methods. A retrospective cohort was assembled, comprising 200 patients with SLE from 5 centers. This cobort was balanced in terms of race and SES. Patients provided information on socioeconomic factors, access to health care, nutrition, self-efficacy for disease management, health locus of control, social support, compliance, knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
193
5
5

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 212 publications
(210 citation statements)
references
References 42 publications
7
193
5
5
Order By: Relevance
“…Global physical function was improved by 7 points on the SF-36; although this change was not statistically significant, it is greater than the minimum clinically significant change suggested for interpreting change scores in rheumatoid arthritis trials (59). The clinical trial results confirm cross-sectional findings from research done by our group and other investigators, and support the importance of psychosocial factors in outcome in SLE (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Global physical function was improved by 7 points on the SF-36; although this change was not statistically significant, it is greater than the minimum clinically significant change suggested for interpreting change scores in rheumatoid arthritis trials (59). The clinical trial results confirm cross-sectional findings from research done by our group and other investigators, and support the importance of psychosocial factors in outcome in SLE (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 70%
“…Self-efficacy has been correlated with SLE outcome in several studies (8)(9)(10)(11)(12)(13)(14)(15) and has been found to consistently predict health-related outcomes in prospective studies (60). In this trial, we demonstrated that self-efficacy could be enhanced by our intervention and that it was a key predictor of mental health status and fatigue outcomes.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations